Bisphosphonic acids and related compounds as inhibitors of nucleotide‐ and polyphosphate‐processing enzymes: A PPK1 and PPK2 case study. (28th November 2018) - Burda‐Grabowska, Małgorzata; Macegoniuk, Katarzyna; Flick, Robert; Nocek, Boguslaw P.; Joachimiak, Andrzej; Yakunin, Alexander F.; Mucha, Artur; Berlicki, Łukasz
Abstract: Bisphosphonic acids, which are structural analogs of pyrophosphate, constitute a class of compounds with very high potential for the construction of effective inhibitors of enzymes operating on oligo‐ and polyphosphates. The bisphosphonate‐based methodology was applied for the discovery of inhibitors of two families of polyphosphate kinases (PPK1 and PPK2). Screening of thirty‐two structurally diverse bisphosphonic acids and related compounds revealed several micromolar inhibitors of both enzymes. Importantly, selectivity of bisphosphonates could be achieved by application of the appropriate side chain. Abstract : The bisphosphonate‐based methodology was applied for the discovery of inhibitors of two families of polyphosphate kinases (PPK1 and PPK2). Screening of thirty‐two structurally diverse bisphosphonic acids and related compounds revealed several micromolar inhibitors of both enzymes.